BREAST CRYPTOCOCCOSIS IN IMMUNOCOMPETENT PATIENTS - Fiori, Mariana; Calvano Filho, Carlos Marino Cabral; Pereira, Pollyanna Dornelas; Fernandes, Marco Vinícius; Souza, Daniela Omar de (Mastology, 2021)
Introduction: Cryptococcosis is prevalent in immunocompromised individuals. Immunocompetent patients can develop latent infections, the breast being a rare focus of primary disease, with few reports in the literature. Case report: GHMC, female, 27 years old, married, ticketing operator, resident in Valparaíso / GO, Brazil. She denied comorbidities, use of medication, smoking or drinking, as well as contact with caves, farms, farms, wild animals and ingestion of game meat. She reported fever (38°C), left mastalgia associated with hardened erythema with subsequent fistulization and removal of purulent secretion. Upon examination, she was in good general condition, with a palpable nodule of about 6 x 4 cm, in union of the lower quadrants (ULQ) of the left breast (LB), which was regular, soft, felt a little painful on palpation, with increased local temperature and without lymph node enlargement or papillary discharge. The ultrasound of the breasts showed a heterogeneous solid mass, with cystic areas of permeation, in ULQ of LB, of 4.2x2.2 cm, partially defined con - tours coinciding with a nodular image of 4 cm in the same topography in the mammography. Magnetic resonance imag- ing showed a nodular, irregular, hypodense image in T1, hyperdense in T2, with parietal enhancement and heteroge - neous, progressive internal enhancement, in addition to capturing septa, measuring 6.1x4.0x4.6 cm, suggesting mucinous carcinoma. Core biopsy of the solid part of the lesion and collection of mucinous fluid was performed. Concomitantly, oxacillin was started for seven days. There was no laboratory change during the entire disease period. Fifteen days after the end of the antibiotic use, the lesion became an erythematous lenticular ulcer, with flat edges, of 5.0x4.0 cm, with col- loid secretion leaving its bed. Histology showed cryptococcosis, and liquid cytology showed cryptococcus neoformans. During immunosuppression investigation, the patient underwent chest and skull CT scans, serology, tumor markers, ANF (antinuclear factor), rheumatoid factor, C3, C4, lumbar puncture and blood cultures (all excluded any immunosup- pressive pathology). The treatment was carried out with Fluconazole 800 mg/day for three months, with a reduction to 300mg/day for another three months. Two months after the start of treatment, the lesion resolved. Cryptococcosis is an invasive mycosis with high morbidity and mortality. It affects immunosuppressed individuals, and is rare in immuno - competent individuals. The main pathogenic species, C. neoformans and C. gatti, are prevalent in tropical and subtropical climates. The main sites affected are the brain and the lungs; other sites are rare. The dosage and duration of breast therapy is unknown, but 2-3g/day of amphotericin B or 400-800mg/day of fluconazole for 8–12 weeks has achieved therapeutic success in reported cases.